PERAN KEPEMIMPINAN KYAI DALAM MEMBENTUK KARAKTER RELIGIUS SANTRI DI PONDOK PESANTREN ALBURHAN SUKAWENING GARUT - Sahid Maulana Sidiq; Iman Saifullah; Anton Anton (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of the Kyai's leadership in shaping the religious character of students (santri) at Al-Burhan Islamic Boarding School, Sukawening, Garut. The study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews with the Kyai, teachers (ustadz), and students, as well as documentation studies. The data were analyzed through the processes of data reduction, data display, and conclusion drawing. The findings reveal that the Kyai’s leadership plays a crucial role in the development of students’ religious character through exemplary behavior, habituation of religious practices, moral guidance, advice-giving, and supervision of students’ daily activities. The formation of religious character is carried out in an integrated manner through various religious activities and pesantren cultural practices that support the development of faith, discipline, responsibility, and noble morals. Supporting factors in this process include the Kyai’s exemplary leadership, a conducive boarding school environment, and the support of teachers and pesantren administrators. Meanwhile, inhibiting factors include external environmental influences, the rapid development of information technology, and the diverse backgrounds of students. These findings provide insights for improving character education programs. The study also highlights the importance of collaboration among parents, teachers, and community members in supporting students' character development sustainably.